Implementation of Clinical Supervision in Enhancing Teacher Professionalism - Eka Lazuardi; Rian Hidayat; Nasution, Zubeir Ahmad; Lilia Ulya Amalia; Syafaruddin (Journal of Practice Learning and Educational Development, 2026)
Teachers are professional educators. To carry out their duties in educating students, teachers must have sufficient competence. This study aims to improve the teaching and learning process carried out by teachers through a series of systematic improvements to improve professional competence. This study examines the characteristics of clinical supervision, procedures in carrying out clinical supervision and the strengths and weaknesses of clinical supervision. This research is library research by collecting data by analyzing books related to the research topic. The results of the study show the formation of professionalism from teachers who intend to support education reform and to "combat" educational decline, especially starting with teaching teachers in the classroom. With repairs and improvements, it is hoped that students can study well so that educational and teaching goals can be achieved optimally. especially in teaching performance based on observation and analysis of accurate and objective data as a guide for changing teaching behavior. This supervision puts emphasis on the process of "professional development and development" with the intention of responding to the main understanding and needs of teachers related to their duties.